(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to provide a clear framework for the concept of knowledge management as an attempt to deepen understanding of this subject, as well as to identify the requirements for its application in the Central Library of the University of Mosul, and to determine their availability there. The researcher used the survey method that is appropriate for this study, and adopted the stratified random sample method on a sample of library workers, and used the questionnaire as a main tool for data collection, and the study data were processed statistically using the software package (SPSS). One of the most important results of the study is the absence of workshops related to the concept of knowledge management. Therefore, the majority of workers at different functional and administrative levels do not have a clear vision of the concept of knowledge management and the importance of its application to achieve the goals of the library.